Minnaert, Anja y Endara, Gustavo (coords.). (2015). Democracia participativa e izquierdas: logros, contradicciones y desafíos. Quito: FES-ILDIS. - Rodrigues de Caires, Carlos Miguel (Estudios Políticos, 2017)
.